Comparison of non invasive ventilation and high-flow nasal cannula oxygenation in patients with covid-19: A randomized clinical study - S.D. Pratibha; L.K. Shivanand; Renuka Holyachi; K. Nirmaladevi; N.R Swathi; Vidya Patil (Al Ameen Medical College, 2023)
Introduction: Non invasive ventilation (NIV) is a pressure-targeted modality and due to pressure efficacy of NIV is determined. High-flow nasal cannula (HFNC) is a non invasive ventilator which provides oxygenation with high flow and is well-tolerated assist device. There are limited studies comparing the effect of two methods of oxygen administration among covid-19 patients. Hence this study was conducted to compare the use of HFNC and NIV as first line of treatment in covid -19 patients with respiratory failure. Methods: This study was done on 82 patients diagnosed with covid-19 infection, 41 patients in NIV group and 41 patients in HFNC group. Patients with rtPCR positive in hypoxemic respiratory failure who require NIV or HFNC as first line of treatment, patients aged between 20-60 years and weighing between 40-80kgs were included in the study. Results: There was no significant difference statistically in regards to mean heart rate, mean respiratory rate, pH and PaCO2 .There was no significant statistical difference in oxygen saturation (Spo2) from admission till 48 hours in between the two groups and there was statistically significant difference from 48 hours of admission to day 6. In NIV group, 4.9% required intubation and in HFNC group 19.5% required intubation. Conclusion: Patients who are diagnosed with covid-19 and in acutehypoxemic respiratory failure can be treated either with NIV or HFNC as a first line of treatment. NIV is more effective in terms of improvement in saturation, reduced respiratory rate and decrease in ICU stay with good haemodynamic stabilty. NIV group had less intubation rate and more compliance compared to HFNC group.